2004
DOI: 10.1590/s0036-46652004000500009
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioidomycosis in organ transplant recipient: case report

Abstract: SUMMARYParacoccidioidomycosis is a common disease in Latin America but it is rare in organ transplant recipient patients. We report on a case of such mycosis in a renal transplant recipient. The patient presented with a large lung cavity on the left lower lobe, a rare radiological presentation of paracoccidioidomycosis. Unusual clinical and radiological manifestations of Paracoccidioides brasiliensis infection can occur in immunocompromised patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 5 publications
0
25
0
2
Order By: Relevance
“…In a small number of cases, PCM manifested a few days to 14 years after kidney transplantation, which enabled the evaluation of PCM's clinical and laboratory characteristics under these conditions. Chest X-rays revealed that these patients had bilateral nodules 18 , pulmonary cavitation 71,72 , or bronchopneumonic infiltrate 73 . Lymphatic impairment was uncommon 74 .…”
Section: Organ Transplantation and Immunosuppressive Therapymentioning
confidence: 95%
“…In a small number of cases, PCM manifested a few days to 14 years after kidney transplantation, which enabled the evaluation of PCM's clinical and laboratory characteristics under these conditions. Chest X-rays revealed that these patients had bilateral nodules 18 , pulmonary cavitation 71,72 , or bronchopneumonic infiltrate 73 . Lymphatic impairment was uncommon 74 .…”
Section: Organ Transplantation and Immunosuppressive Therapymentioning
confidence: 95%
“…Only three cases of paracoccidioidomycosis in SOT recipients have been reported, and all occurred in renal transplant patients (339,353,417). In all cases, infection developed more than 5 years after transplantation, and clinical presentations were similar to those of other cases of this mycosis in nonimmunosuppressed patients.…”
Section: Other Regional Fungal Infectionsmentioning
confidence: 82%
“…In all cases, infection developed more than 5 years after transplantation, and clinical presentations were similar to those of other cases of this mycosis in nonimmunosuppressed patients. Exceptionally, one patient was found to have cavitating lung lesions, which is infrequent in immunocompetent patients (417).…”
Section: Other Regional Fungal Infectionsmentioning
confidence: 95%
“…P. brasiliensis is a thermally dimorphic fungus that typically infects healthy adults. Infection primarily involves the lungs and then disseminates to other organs 5 . Paracoccidioidomycosis is very rare in transplanted patients and a limited number of reports have been described in kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%